Advancing agriculture with functional NM: “pathways to sustainable and smart farming technologies” - Mir Waqas Alam; Pir Mohammad Junaid; Yonis Gulzar; Buzuayehu Abebe; Mohammed Awad; S. A. Quazi (Discover Nano)
Abstract The integration of nanotechnology in agriculture offers a transformative approach to improving crop yields, resource efficiency, and ecological sustainability. This review highlights the application of functional NM, such as nano-formulated agrochemicals, nanosensors, and slow-release fertilizers, which enhance the effectiveness of fertilizers and pesticides while minimizing environmental impacts. By leveraging the unique properties of NM, agricultural practices can achieve better nutrient absorption, reduced chemical runoff, and improved water conservation. Innovations like nano-priming can enhance seed germination and drought resilience, while nanosensors enable precise monitoring of soil and crop health. Despite the promising commercial potential, significant challenges persist regarding the safety, ecological impact, and regulatory frameworks for nanomaterial use. This review emphasizes the need for comprehensive safety assessments and standardized risk evaluation protocols to ensure the responsible implementation of nanotechnology in agriculture.